2011
DOI: 10.1007/s12576-011-0173-8
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomere length-dependent Ca2+ activation in skinned rabbit psoas muscle fibers: coordinated regulation of thin filament cooperative activation and passive force

Abstract: In skeletal muscle, active force production varies as a function of sarcomere length (SL). It has been considered that this SL dependence results simply from a change in the overlap length between the thick and thin filaments. The purpose of this study was to provide a systematic understanding of the SL-dependent increase in Ca2+ sensitivity in skeletal muscle, by investigating how thin filament “on–off” switching and passive force are involved in the regulation. Rabbit psoas muscles were skinned, and active f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Increasing filament strain is thought to increase thick filament cooperativity (Fusi et al, 2016;Linari et al, 2015). Additionally, tropomyosin activation may be facilitated by neighboring troponin complexes that are already active, the so-called 'thin filament cooperativity' (Fukuda et al, 2011;Terui et al, 2008), which increases with increasing sarcomere length (Fukuda et al, 2011;Terui et al, 2008). We found no difference in length dependence of calcium sensitivity between wild-type and mdm muscles, suggesting no effect of the mdm mutation regardless of the mechanisms involved.…”
Section: Discussion Activation Dependence Of Optimal Length and Lengtmentioning
confidence: 57%
See 2 more Smart Citations
“…Increasing filament strain is thought to increase thick filament cooperativity (Fusi et al, 2016;Linari et al, 2015). Additionally, tropomyosin activation may be facilitated by neighboring troponin complexes that are already active, the so-called 'thin filament cooperativity' (Fukuda et al, 2011;Terui et al, 2008), which increases with increasing sarcomere length (Fukuda et al, 2011;Terui et al, 2008). We found no difference in length dependence of calcium sensitivity between wild-type and mdm muscles, suggesting no effect of the mdm mutation regardless of the mechanisms involved.…”
Section: Discussion Activation Dependence Of Optimal Length and Lengtmentioning
confidence: 57%
“…Current theories have focused instead on length-dependent thick and/or thin filament cooperativity (Fukuda et al, 2011;Terui et al, 2010). Cross-bridge attachment to the thin filaments may be facilitated by neighboring cross-bridges that are already attached, the so-called 'thick filament cooperativity' (Fusi et al, 2016;Linari et al, 2015;Reconditi et al, 2014).…”
Section: Discussion Activation Dependence Of Optimal Length and Lengtmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the underlying mechanism of LDA is still unknown. Different characteristics of the myofilaments contribute to LDA, such as the inter-filament lattice spacing [2426], the distinctive structural changes in thick and thin filaments [27, 28], the orientation and number of cross-bridges [2931], titin-based passive tension [3237], and the increase in positive feedback on myocardial contractile regulation [3840]. Our previous studies have shown that Ca 2+ -induced opening of the N-domain of cTnC [40], and Ca 2+ -induced movement of C-terminus of cTnI [41] are both SL- and cross-bridge-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Among the proteins suggested to contribute to LDA, titin seems to be a particularly strong candidate 2 10 11 12 13 14 . The stiffness of titin could modulate LDA by adding to lattice compression via a radial force component ( F R ) that arises out of stretching the titin springs in the sarcomere ( Fig.…”
mentioning
confidence: 99%